Procamacolaimus dorylaimus sp. nov. (Nematoda: Leptolaimidae) from the Southern Atlantic - Holovachov, O. (Annales Zoologici, 2003)
Procamacolaimus dorylaimus sp. novo is described from the Southern Atlantic (South Shetland Islands, Antarctica). The species is characterised by 3.4-3.5 mm long body; coarsely annulated cuticle without lateral field, epidermal glands and body pores absent, somatic setae present; labial sensilla papilliform, 5.5 /lm long cephalic setae; amphid located anteriorly to cephalic setae bases; ocelli absent; deirid and secretory-excretory system absent; stoma 38-41 /lm long, strongly cuticularised, spear-like; pharynx heavily muscularized, without radial tubules, valves and bulbs; male reproductive system diorchic; spicules 85.5 /lm long, arcuate with ventrally inclined manubrium; gubernaculum complex; 12 tubular supplements, single precloacal setiform sensillum and two subventral postcloacal papilliform sensilla; female reproductive system didelphic, amphidelphic; spermatheca axial, vagina straight; tail conoid, ventrally arcuate; caudal glands present, spinneret small and weakly sclerotized. Procamacolaimus profundus Vitiello, 1974 is transferred to the genus Anguinoides whereas Paraphanolaimus granuliferus Timm, 1963 to Listia. The emended diagnosis, species lists and keys are given for Anguinoides, Procamacolaimus and Listia.
NeMys doc_id: 17873